(untitled) (Eurasian Research Bulletin, 2021)
Pure cashew gums as well as cashew gum contaminated with cashew bark were subjected to oxidation in order to determine the amount of oxidant they consumed. Hydrogen peroxide was the oxidant of choice because its reaction products are water and oxygen. It was observed that while the pure gum consumed a few amount of the oxidant, the dirty gum consumed substantial amount of the oxidant. This preliminary result shows that the oxidant is a promising material for use as cashew gum decontaminant.